Modular neck stems in total hip arthroplasty: current concepts. Issue 9 (14th September 2021) - Solarino, Giuseppe; Vicenti, Giovanni; Carrozzo, Massimiliano; Ottaviani, Guglielmo; Moretti, Biagio; Zagra, Luigi
Abstract : Modular neck (MN) implants can restore the anatomy, especially in deformed hips such as sequelae of development dysplasia. Early designs for MN implants had problems with neck fractures and adverse local tissue, so their use was restricted to limited indications. Results of the latest generation of MN prostheses seem to demonstrate that these problems have been at least mitigated. Given the results of the studies presented in this review, surgeons might consider MN total hip arthroplasty (THA) for a narrower patient selection when a complex reconstruction is required. Long MN THA should be avoided in case of body mass index > 30, and should be used with extreme caution in association with high offset femoral necks with long or extra-long heads. Cr-Co necks should be abandoned, in favour of a titanium alloy connection. Restoring the correct anatomic femoral offset remains a challenge in THA surgeries. MN implants have been introduced to try to solve this problem. The MN design allows surgeons to choose the appropriate degree and length of the neck for desired stability and range of motion. Cite this article: EFORT Open Rev 2021;6:751-758. DOI: 10.1302/2058-5241.6.200064